Atividade antiulcerogênica do extrato aquoso das folhas de Psidium guineense Swartz - SOUSA, Ana Kely Araújo de (2016)
Psidium guineense Swartz (Myrtaceae) is a popular shrub commonly as araçá, araçá do campo, araçá vedaleiro, araçá mirim, araçá pedra ou araçazinho, and is widely distributed in Brazil, taking place in the Amazon, Caatinga, Cerrado and Atlantic Forest. Its barks and roots are used commonly in the treatment of gastrointestinal disorders such as colic, diarrhea, gastroenteritis and gastritis. The phytochemical research reveals that the species is rich in flavonoids and tannins, classes of compounds that have shown potential antiulcerogenic activity. Based on their phytochemical characteristics and in popular usage, the aim of this study was to investigate the antiulcerogenic activity of aqueous extract of Psidium guineense (EAPg) and possible mechanisms involved in this activity. The extract was prepared from the powder by aqueous extraction of the leaves at 60 °C. In acute toxicity, EAPg was administered orally in a single dose (5g/kg). The antiulcer activity of EAPg (125, 250 and 250 mg/kg) was evaluated using models of gastric ulcer induced by etanol 75% (10 mL/kg) or indomethacin (30 mg/kg). Were determined baseline antisecretory activity by the method of pyloric ligation, the involvement of nitric oxide and sulfhydryl compounds, and quantified the levels of gastric mucus and sulfhydryl compounds. The anti-Helicobacter pylori activity was determined by in vitro assay. No signs of toxicity or death was recorded after oral administration of EAPg at a dose of 5.0 g/kg. Oral administration of EAPg (125, 250 and 500 mg/kg) was effective in protecting the gastric mucous membrane, reducing by 45.0, 88.0 and 93.0% gastric lesions induced by ethanol, respectively. Furthermore, EAPg reduced by 53.0, 79.0 and 94.0% gastric ulcer induced by indomethacin, respectively. EAPg (250 mg/kg) increased the pH and reduced the total acidity, but did not change the volume of gastric secretion, suggesting an absence of antisecretory effect. The antiulcerogenic activity EAPg is not related to nitric oxide, but is dependent on the presence of sulfhydryl compounds. The prior administration of EAPg increased basal levels of mucus 89,4% and 78,9% sulfhydryl compounds in the gastric mucosa, thus confirming their cytoprotective activity. The EAPg showed no bactericidal activity against Helicobacter pylori, having a minimum inhibitory concentration (MIC) 2000 mg/mL. The results showed that the aqueous extract of Psidium guineense has antiulcer activity. In addition, they contribute to a better understanding of the species and to validate the use of this species in the treatment of gastrointestinal disorders